Analisis Pengetahuan Dan Pandangan Mahasiswa Tentang Sistem Informatika Dalam Menentukan Tinggi Rendahnya Harapan Kepada Mahasiswa Dalam Pencegahan Tindak Pidana Korupsi Dilingkungan Kampus - Nur, Aryanto (CV. ITTC INDONESIA, 2025)
Corruption not only hinders development and welfare, but also weakens public trust in an institution, whether government, private, or institutional. This study aims to conduct research related to criminal acts and prevention of corruption by implementing information systems in the campus world. This research is expected to help monitor the management of campus institutional funds. Research is also expected to be able to explain existing theories. This research can be used as a reference for further research. Adequate student knowledge and views and the use of information systems by students are expected to prevent criminal acts of corruption in the campus institutional environment. The approach used in this study is descriptive statistics which describes the research results in the form of discussions. The sampling technique in this study is non-probability sampling, the types of data used in this study are primary data and secondary data. The data analysis method in this study uses smartpls - partial least square (PLS) analysis. The location or target of respondents in this study are several universities in the DKI Jakarta area. This research is a quantitative study with a descriptive design. With a survey method involving 50 respondents at various universities in DKI Jakarta. The results of this study show the influence of student knowledge and views on information systems in preventing criminal acts of corruption.